Synthesis of Chitosan/Poly (Diethyl aminoethyl methacrylate) Interpenetrating Polymer Network Gels - Alizor, Nwaka Esther (My University, 2015)
In this study, chitosan was cross-linked with glutaraldehyde to prepare semi-IPN (SIPN) and IPN hydrogel systems. Several interpenetrating polymer network (IPNs) type hydrogels from the mixture of chitosan, diethylamino ethylmethacrylate (DEAEM), potassium persulphate, N,N′- methylenebisacrylamide (MBA) of pH responsive swelling properties were synthesized by in-situ polymerization method. The IPN and semi-IPN (SIPN) gels prepared were characterized by swelling characteristics at 37 °C, and also by scanning electron microscopy (SEM). The SEM image of the semi-IPN gel shows smoother morphology while that of the IPNs gives rougher surface with smaller pores. The hydrogels obtained exhibit pH sensitive swelling behavior. All samples swell highest in acidic medium. The equilibrium swelling values obtained at pH 1, 7 and 11 respectively are as follows: IPN (822%)> SIPN (783%) > CH (173%), IPN (453%)> SIPN (235%)> CH (119%) IPN (425%)> SIPN (242%) > CH(78%). The drug ciprofloxacin was loaded into the IPN hydrogels in water. Drug release kinetics were followed in pH 1.2 buffer solution at 37 °C.

ÖZ: Bu çalışmada , kitosan glutaldehit ile çapraz bağlanıp yarı iç-içe girmiş polimerik ağ yapılar ile iç-içe girmiş polimerik ağ yapılarının sentezi ile hidrojeller hazırlandı. pH duyarlı çeşitli polimerik ağlar kitosanın dietilamino etilmetakrilat (DEAEM), potasyum persülfat , N , N'- metilenbisakrilamid (MBA) ile in-situ polimerizasyon yöntemi ile sentezlenmiştir. Hazırlanan yarı iç-içe girmiş polimerik ağ yapılar ile iç-içe girmiş polimerik ağ yapılarının 37 °C 'de şişme özellikleri incelenmiş ve taramalı elektron mikrokopu ile morfolojileri karakterize edilmiştir. Elektron mikroskopu analizlerinden iç-içe girmiş polimerik ağ yapılarının küçük gözeneklere sahip pürüzlü bir yüzeye sahip olduğu gözlemlenirken yarı iç-içe girmiş polimerik ağ yapılarının SEM görüntüsü daha az pürüzlü morfoloji göstermektedir . Hidrojellerin pH duyarlı şişme davranışı gösterdiği saptandı. Bütün numuneler, asidik ortam içinde en yüksek oranda şişme gösterirken. Denge şişme% değerleri pH 1 , 7 ve 11 de elde edilmiş ve aşağıda sırasıyla belirtilmiştir: IPN ( 822 %) > SIPN ( 783 %) > CH ( 173 %) , IPN ( 453 %) > SIPN ( % 235) > CH ( 119 %) IPN ( 425 %) > SIPN ( 242 %) > CH ( % 78). Siprofloksasin antibiyotik ilaç suda hazırlanan hidrojellere yüklenerek ilaç salım kinetiği , 37 ° C'de pH 1.2 tampon çözeltisi içinde takip edilmiştir.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2015. Supervisor: Prof. Dr. Elvan Yılmaz.
Keywords: Chemistry; Interpenetrating polymer network, glutaraldehyde, chitosan, ciprofloxacin, hydrogels